Slivers of Hope: Women in Dystopian Trilogy - Josephine May Grace Aclan Famoso (Universitas Ahmad Dahlan, 2021)
This paper explores the struggles, goals, and motivations of the women characters in The Hunger Games Trilogy. In detail, the study employs Elaine Showalter’s Feminist theory to reveal the women characters’ categories in terms of three stages: feminine, feminist and female. In the study, some of the women characters living in the dehumanized society of Panem have attained the last stage of feminism which is the female stage. However, other women characters are not able to fulfill their goals. Still, due to the women characters’ demand to change the system, they start an uprising. For example, the main character, Katniss Everdeen, contributes to the collapse of the ruling government in power as she accepts being the Mockingjay, the symbol of revolution. Another woman character to exemplify such a noble act is Johanna Mason who becomes part of the rebellion and survives the war against the unjust ruling of the Capitol. These women characters are slivers of light amidst the chaos. In conclusion, it is discovered that women characters play pivotal roles in society. This suggests that women characters recognize their power to accelerate societal advancement. For this dystopian trilogy, in particular, women become symbols of hope.